2020
DOI: 10.3390/e22101176
|View full text |Cite
|
Sign up to set email alerts
|

Transfer Entropy Analysis of Interactions between Bats Using Position and Echolocation Data

Abstract: Many animal species, including many species of bats, exhibit collective behavior where groups of individuals coordinate their motion. Bats are unique among these animals in that they use the active sensing mechanism of echolocation as their primary means of navigation. Due to their use of echolocation in large groups, bats run the risk of signal interference from sonar jamming. However, several species of bats have developed strategies to prevent interference, which may lead to different behavior when flying w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
4
0
1
Order By: Relevance
“…Finally, an emerging line of inquiry into the properties of animal groups that has not yet gained much traction in the physics community but that may prove to be very valuable is the use of techniques from information theory to try to make inferences about the flow of information in the group [107]. The most common quantity that has been used for this purpose is the transfer entropy, which provides an estimate of how much information flows from one individual to another and has been used to study leader-follower relationships in bats [108,109]. Accurate estimates of the transfer entropy require long time series and large data ensembles, and so it has not yet become a widely used tool.…”
Section: Relative Statisticsmentioning
confidence: 99%
“…Finally, an emerging line of inquiry into the properties of animal groups that has not yet gained much traction in the physics community but that may prove to be very valuable is the use of techniques from information theory to try to make inferences about the flow of information in the group [107]. The most common quantity that has been used for this purpose is the transfer entropy, which provides an estimate of how much information flows from one individual to another and has been used to study leader-follower relationships in bats [108,109]. Accurate estimates of the transfer entropy require long time series and large data ensembles, and so it has not yet become a widely used tool.…”
Section: Relative Statisticsmentioning
confidence: 99%
“…Specifically, transfer entropy (TE) and conditional transfer entropy (CTE) can quantify coupling between time-series variables, and therefore identify candidate variables for a model. These metrics have found successful applications in the study of various complex systems including human brain activity [24][25][26], animal collective behavior [27][28][29][30][31], climate modeling [32], policy-making [33][34][35][36][37] and financial markets [38,39]. However, its application within vehicular traffic systems has been relatively limited [40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the higher-dimensional joint probabilities involved, accurately estimating the transfer entropy is a nontrivial task. The k-nearest neighbors estimator for mutual information first proposed by Kraskov, Stögbauer, and Grassberger [19] (henceforth abbreviated as the KSG estimator) has become the standard in many information theory studies [20][21][22]; but, although the algorithm can be straightforwardly generalized to estimate transfer entropy, it has been shown that this generalization reduces the accuracy of the method [23]. Alternative estimation schemes do exist, such as the use of kernel density estimators, but comparative studies have found them to perform, at best, only marginally better than the KSG method [24,25].…”
Section: Introductionmentioning
confidence: 99%